Innovative thinking and its relation with the mental Rotation among at the university students - كاظم سلمان, بشرى; طرار غند, ياسين (Journal of College of Education, 2020)
A student at the University of Mustansiriya at the University of Mustansiriya for the academic year (2018/2019), was chosen in a mixed way, and the goal of achieving the goal of the study carried out by the researcher adopted the Torrance Test for Innovative Thinking and the translation of the test Jawa (1973) modified by Jun (2011) The researcher admitted the test on Computer, the results of the study results in the colonel. Innovative and mental cycling. In light of these results, the researcher presented.
Keywords: Key word: Innovative thinking, mental Rotation.